2010
DOI: 10.1016/j.cell.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Signaling Specifies Axons during Brain Development

Abstract: In the mammalian brain, the specification of a single axon and multiple dendrites occurs early in the differentiation of most neuron types. Numerous intracellular signaling events for axon specification have been described in detail. However, the identity of the extracellular factor(s) that initiate neuronal polarity in vivo is unknown. Here, we report that transforming growth factor-β (TGF-β) initiates signaling pathways both in vivo and in vitro to fate naïve neurites into axons. Neocortical neurons lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
256
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(268 citation statements)
references
References 57 publications
11
256
1
Order By: Relevance
“…TGF-b1, TGF-b2, and TGF-b3 have also been shown to increase the number and length of neurites . Together, these findings indicate that TGF-b signaling is required to induce axon formation and neuronal migration (Yi et al 2010).…”
Section: Migration and Axon Guidancementioning
confidence: 74%
“…TGF-b1, TGF-b2, and TGF-b3 have also been shown to increase the number and length of neurites . Together, these findings indicate that TGF-b signaling is required to induce axon formation and neuronal migration (Yi et al 2010).…”
Section: Migration and Axon Guidancementioning
confidence: 74%
“…63). In addition, recent findings demonstrate that Tgfbr2 activity is required for axon formation and neuronal migration in the developing mammalian neocortex (64) and that expression of Fgfr1 and Fgfr2 determines brain size (65,66). Richtsmeier et al (67) have pointed out the analogy between human craniosynostosis and the simplification trend of cranial bone elements in synapsid evolution.…”
Section: Discussionmentioning
confidence: 99%
“…6G-K). Co-activation of mitochondrial biogenesis is also a prerequisite for TGFβ-TAK1-induced neuronal growth TAK1, activated by TGFβ signalling, controls axonal growth during brain development (Yi et al, 2010). However, it has also been shown that TAK1 activates AMPK (Xie et al, 2006).…”
Section: Activation Of Mitochondrial Biogenesis Is Required For Ampkimentioning
confidence: 99%